Inquiry into the potential value of an information pamphlet on consent to surgery to improve surgeon-patient communication. Issue 2 (June 1998) - Meredith, P; Wood, C
Abstract : OBJECTIVES: To find out how patients recently undergoing surgery experienced the consenting process and the response of these patients to a pamphlet on consent to surgery. To test the reaction of health professionals to the pamphlet. DESIGN: A pilot pamphlet was produced and a questionnaire was sent to patients inquiring about their consenting experience, and how the pamphlet might have helped them through the consent procedure. A pamphlet and a questionnaire were also sent to a random sample of the health professionals serving these patients. SUBJECTS: Patients and health professionals. RESULTS: 61% of patients returned the questionnaire. Knowledge about the consent procedure was shown to be limited. 49% were unaware that they had the right to insist that the surgeon could only perform the specified operation and nothing more. 83% were unaware that they could add something in writing to the consent form before signing. 28% of health professionals returned their questionnaire, most of whom thought that the pamphlet provided a useful contribution to surgeon-patient communication. CONCLUSION: Evidence shows that patients are not well informed about consenting to surgery and further information would provide much needed guidance on understanding their role in the consent procedure. The low response from the health professional study is perhaps an indication that at present this is an issue which is not seen as a priority.